Investigation of plane-strain backward extrusion process by means of upper bound method - Plančak, Miroslav; Bramley, Alan; Osman, F. (Journal of Production Engineering, 1989)
The process of backward extrusion in a plane strain condition was investigated using the upper bound method. A kinematically admissible velocity field was assumed inside the material beneath the punch, satisfying the boundary conditions. Total energy was calculated, and optimization with respect to the height of the deformation zone was performed. The results were compared with experiments, and a good agreement was achieved.